2000
DOI: 10.1128/mcb.20.9.3198-3209.2000
|View full text |Cite
|
Sign up to set email alerts
|

Protein Zero Gene Expression Is Regulated by the Glial Transcription Factor Sox10

Abstract: Myelinating glia express high levels of a unique set of genes which code for structural proteins of the myelin sheath. Few transcription factors have so far been implicated in the regulation of any myelin gene. Here we show that the protein zero (P 0 ) gene, a myelin gene exclusively expressed in the Schwann cell lineage of the peripheral nervous system, is controlled in its expression by the high-mobility-group domain protein Sox10 both in tissue culture and in vivo. Induction of wild-type Sox10, but not of o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
221
0
2

Year Published

2000
2000
2005
2005

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 209 publications
(233 citation statements)
references
References 53 publications
10
221
0
2
Order By: Relevance
“…This antiserum recognizes an epitope at amino acids 165-181 of human SOX10; therefore, the signals were quantitative for both wild-type SOX10 and the truncated proteins used in this study. We used oligonucleotide probes containing a single SOX10-binding site (site B) 43 for EMSAs.…”
Section: Methodsmentioning
confidence: 99%
“…This antiserum recognizes an epitope at amino acids 165-181 of human SOX10; therefore, the signals were quantitative for both wild-type SOX10 and the truncated proteins used in this study. We used oligonucleotide probes containing a single SOX10-binding site (site B) 43 for EMSAs.…”
Section: Methodsmentioning
confidence: 99%
“…The B16/F10.9 cells express endogenous Sox10, an HMG factor found to be important in both melanocytic (45)(46)(47)(48) and SC differentiation (15,16,49). An increase in Sox10 RNA was observed by RT-PCR with RNA extracted 72 h after IL6RIL6 addition to the cells (Fig.…”
Section: Transcriptional Activation Of Myelin Po and Mbp Gene Promotementioning
confidence: 99%
“…15 for review). Thus, the high mobility group (HMG) domain Sox10, already present in early neural crest cells, activates the Po promoter (16). Krox20/Egr2, a late marker of myelinating SC differentiation required for myelination (17), stimulates expression of several myelin genes (18,19).…”
mentioning
confidence: 99%
“…The analysis of Sox10 gene function using mutant mammalian models is hampered because Sox10 Dom /Sox10 Dom and Sox10 LacZ /Sox10 LacZ embryos die before birth (Lane andLiu, 1984, Britsch et al, 2001). Although it has been demonstrated that Sox10 is critical for survival of several NC-derived lineages (Southard-Smith et al, 1998;Britsch et al, 2001;Potterf et al, 2001) and several downstream target genes have been identified Lang et al, 2000;Lee et al, 2000;Peirano et al, 2000;Potterf et al, 2000Potterf et al, , 2001Bondurand et al, 2001;Britsch et al, 2001), the functional roles of SOX10 in the development of NC-derived lineages is not completely understood.…”
Section: Introductionmentioning
confidence: 99%